Concepts of Life Health Education Included in Science Books for the First Three Grades from the Point of View of Teachers of the Basic Stage in Qasaba As-Salt: - - Alsaideh, Jehad Ali; Al-Saidah, Maha Hamed (Dirasat: Educational Sciences, 2023)
Objectives: The study aimed to investigate to what extent the daily health concepts are included in science circular for the first three grades from teachers’ point of view in Qasabat As-Salt. Methods: Descriptive approach was used, and the study population consisted of all science female teachers of the primary stage in public schools in Qasaba Al-Salt in Al-Balqa Governorate. The study conducted in the first semester of the academic year 2022/2023. (176) questionnaires completed out of (200) which were distributed. The questionnaire consisted of four domains that included healthy nutrition, physical health, environmental health, and psychological and social health. Validity and reliability were calculated. Results: The results revealed that there is a high degree of inclusion of daily health concepts in science textbooks for the first three grades. Physical health domain came at the first place, mental and social health came in second place, nutrition came in third place, and environmental health came in last place. The results also showed that there were statistically significant differences at the level (α = 0.05) in the responses according to the academic qualification in favor of bachelor's degree. Conclusion: To enhance the effectiveness of employing the educational content of science in the student's daily life and linking it to healthy life skills, the study recommends conducting further studies considering linking it to the students' life skills. This can include teaching methods and analyzing the contents of science books for other grades.